Pore pressure estimation from seismic velocities - Pérez, Zayra; Ojeda, German Y.; Mateus, Darwin (CT&F - Ciencia, Tecnología y Futuro, 2009)
On pore pressure calculations it is common to obtain a profile in a wellbore, which is then extrapolated toward offset wells. This practice might generate mistakes on pore pressure measurements, since geological conditions may change from a wellbore to another, even into the same basin. Therefore, it is important to use other tools which allow engineers not only to detect and estimate in an indirect way overpressure zones, but also to keep a lateral tracking of possible changes that may affect those values in the different formations. Taking into account this situation, we applied a methodology that estimates formation pressure from 3D seismic velocities by using the Eaton method. First, we estimated formation pore pressure; then, we identified possible overpressure zones. Finally, those results obtained from seismic information were analyzed involving well logs and pore pressure tests, in order to compare real data with prediction based on seismic information from the Colombian foothill.